Benzene absorption in a protuberant-grid-type zinc(ii)–organic framework triggered by the migration of guest water molecules. Issue 1 (11th November 2014) - Tseng, Tien-Wen; Luo, Tzuoo-Tsair; Tsai, Chang-Hsiu; Chen, Chun-Chi; Lee, Gene-Hsiang; Wang, Chih-Chieh; Lu, Kuang-Lieh
Abstract : Benzene molecules are reported to be easily and regularly absorbed into specific channels in a 2D protuberant-grid-type Zn(ii )–organic framework, which consists of racemic interdigitated bilayers. Abstract : The 2D protuberant-grid-type Zn(ii )–organic framework consists of unusual racemic interdigitated bilayers and comprises a 3D intersecting channel system. The framework is thermally stable and the channels contain multiple water aggregates. Accompanying the migration of guest water molecules, only the specific channels in the bilayers along the b axis can easily and efficiently absorb guest benzene molecules in a regular manner.